Manufacturing method of active material mixture for electrode, electrode, and battery

JP2025041463APending Publication Date: 2025-03-26TOYOTA BATTERY CO LTD
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
JP2023148779
Authority / Receiving Office
JP · JP
Patent Type
Applications
Current Assignee / Owner
Filing Date
2023-09-13
Publication Date
2025-03-26

Smart Images

  • Figure 2025041463000003
    Figure 2025041463000003
  • Figure 2025041463000004
    Figure 2025041463000004
  • Figure 2025041463000001
    Figure 2025041463000001
Patent Text Reader

Abstract

To provide a manufacturing method of an active material mixture for an electrode, capable of obtaining an electrode having an excellent penetration resistance and a battery resistance.SOLUTION: A manufacturing method of an active material mixture for an electrode, contains steps of: preparing an active material and a fiber-like conductive carbon material; and adding the fiber-like conductive carbon material into the active material under the following conditions (i) to (iii). The condition (i) is that the fiber-like conductive carbon material is added into the active material in the case where a mean particle diameter of the fiber-like conductive carbon material is a reference A or more and a reference B or less. The condition (ii) is that the fiber-like conductive carbon material and the fiber-like conductive carbon material of which the mean particle diameter exceeds the reference B are mixed and are added to the active material in the case where the mean particle diameter of the fiber-like conductive carbon material is less than the reference A. The condition (iii) is that the fiber-like conductive carbon material and the fiber-like conductive carbon material of which the mean particle diameter is less than the reference A are mixed and are added to the active material in the case where the mean particle diameter of the fiber-like conductive carbon material exceeds the reference B.SELECTED DRAWING: None
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present disclosure relates to a method for making an active material mixture for an electrode, an electrode, and a battery. [Background technology]

[0002] A conductive additive may be added to the active material used in the battery electrodes to improve the performance of the electrodes.

[0003] For example, Patent Document 1 describes a negative electrode material including a negative electrode active material, a conductive assistant, and a binder, the conductive assistant including a conductive assistant A and a conductive assistant B, the conductive assistant B being fibrous carbon having a diameter of 2 nm or more and less than 100 nm and an aspect ratio (B) expressed as (length / diameter) of 30 to 10,000, the conductive assistant B having a nonlinear shape different from the conductive assistant A, the conductive assistant A being fibrous carbon having a diameter of 1 nm or more and less than 1,0 ... having a diameter of 1 nm or more and less than 1,000 nm and an aspect ratio (B) expressed as (length / diameter) of 30 to 10,000, the conductive assistant B having a nonlinear shape different from the conductive assistant A, the conductive assistant A having a diameter of 1 nm or more and less than 1,000 nm and an aspect ratio (B) expressed as (length / diameter) of 30 to 10,000, the conductive assistant B having a nonlinear shape different from the conductive assistant A, the conductive assistant A having a diameter of 1 nm or more and less than 1,000 nm and an aspect ratio (B) expressed as (length / diameter) of 30 to 10,000 the conductive assistant A has a linear or nearly linear shape, the aspect ratio (B) is greater than the aspect ratio (A), the diameter of the conductive assistant A is greater than the diameter of the conductive assistant B, the negative electrode active material has a particulate shape, and a ratio δ, represented by (average particle diameter of the negative electrode active material / length of the conductive assistant B), is 0.15 to 10. [Prior art documents] [Patent documents]

[0004] [Patent Document 1] International Publication No. 2017-061514 Summary of the Invention [Problem to be solved by the invention]

[0005] Fibrous conductive carbon materials are added to the active material used in electrodes. However, fibrous conductive carbon materials generally have a large variation in particle size, and this variation in particle size has a large effect on the penetration resistance and battery resistance. Although a method of selecting (for example, sieving) only fibrous conductive carbon materials having a particle size within a suitable range and using them is conceivable, this increases the number of steps for selection and also results in fibrous conductive carbon materials with large or small particle sizes being discarded without being used, which increases costs. It is therefore desirable to obtain an electrode having excellent penetration resistance and battery resistance without having to select and use only those fibrous conductive carbon materials having a particle size within a suitable range from the prepared fibrous conductive carbon material.

[0006] In view of the above circumstances, an object of one embodiment of the present disclosure is to provide a method for producing an active material mixture for an electrode, which can result in an electrode having excellent through-hole resistance and battery resistance, and an electrode and a battery including the active material mixture obtained by the method for producing the active material mixture. [Means for solving the problem]

[0007] Means for solving the above problems include the following means. <1> Preparing an active material; Providing a fibrous conductive carbon material; adding the fibrous conductive carbon material to the active material according to the following conditions (i) to (iii); A method for producing an active material mixture for an electrode, comprising: (i) When the average particle size of the fibrous conductive carbon material is equal to or larger than criterion A and equal to or smaller than criterion B, the fibrous conductive carbon material is added to the active material. (ii) When the average particle size of the fibrous conductive carbon material is less than the criterion A, the fibrous conductive carbon material C Sii and a fibrous conductive carbon material C having an average particle size exceeding the standard B. Lii and mixing the fibrous conductive carbon material mixture. ii and preparing the fibrous conductive carbon material mixture. iiis added to the active material. (iii) When the average particle size of the fibrous conductive carbon material exceeds the criterion B, the fibrous conductive carbon material C Liii and a fibrous conductive carbon material C having an average particle size less than the standard A. Siii and mixing the fibrous conductive carbon material mixture. iii and preparing the fibrous conductive carbon material mixture. iii is added to the active material. <2> The criteria A and B are determined by the following determination method [1]. <1> 2. A method for producing an active material mixture for an electrode according to claim 1 . (Method for determining Criteria A and Criteria B [1]) A fibrous conductive carbon material is mixed with an active material to prepare an active material mixture, and then a battery is prepared using the active material mixture to measure the battery resistance. This is carried out for three or more types of fibrous conductive carbon materials having different average particle sizes, and a graph is created showing the correlation between the average particle size of the fibrous conductive carbon material and the battery resistance. The average particle sizes of the fibrous conductive carbon material within a range in which the battery resistance exceeds a certain value in the graph are designated as criterion A and criterion B. <3> The criteria A and B are determined by the following determination method [2]. <1> or <2> 2. A method for producing an active material mixture for an electrode according to claim 1 . (Method of determining Criteria A and Criteria B [2]) The fibrous conductive carbon material is mixed with an active material to prepare an active material mixture, and then a battery is prepared using the active material mixture to measure the battery resistance. This is performed for three or more types of the fibrous conductive carbon material having different average particle diameters and three or more types of the active material having different average particle diameters, and a graph showing the correlation between the average particle diameter of the fibrous conductive carbon material and the battery resistance is created for each average particle diameter of the active material. The average particle diameters of the fibrous conductive carbon material within a range in which the battery resistance exceeds a certain value in the graph for each average particle diameter of the active material are defined as criterion A and criterion B. <4> In the step of adding the fibrous conductive carbon material to the active material, Under the condition (ii) above, an index represented by the following formula ii is ii is equal to or greater than the standard A and equal to or less than the standard B, Sii and the fibrous conductive carbon material C Lii and mixing the fibrous conductive carbon material mixture. ii Prepare Under the condition (iii) above, an index represented by the following formula iii is iii is equal to or greater than the standard A and equal to or less than the standard B, Siii and the fibrous conductive carbon material C Liii and mixing the fibrous conductive carbon material mixture. iii preparing <1> ~ <3> 13. A method for producing an active material mixture for an electrode according to claim 12. Formula ii: Index ii = (the fibrous conductive carbon material C Sii × the average particle size of the fibrous conductive carbon material C Sii Addition amount (%) of the fibrous conductive carbon material C Lii × the average particle size of the fibrous conductive carbon material C Lii (%) / 100 Formula III: Index iii = (the fibrous conductive carbon material C Liii × the average particle size of the fibrous conductive carbon material C Liii Addition amount (%) of the fibrous conductive carbon material C Siii × the average particle size of the fibrous conductive carbon material C Siii (%) / 100 <5> preparing an active material having an average particle size of 4.5 μm or more and 8.5 μm or less; preparing a fibrous conductive carbon material having an average particle size of 0.75 μm or more and 1.35 μm or less; adding the fibrous conductive carbon material to the active material according to the following conditions (1) to (3); A method for producing an active material mixture for an electrode, comprising: (1) The average particle size of the active material is 4.5 μm or more and 6.5 μm or less. (1-1) When the average particle diameter of the fibrous conductive carbon material is 0.85 μm or more and 1.15 μm or less, the fibrous conductive carbon material C 11 is added to the active material. (1-2) When the average particle diameter of the fibrous conductive carbon material is less than 0.85 μm, the fibrous conductive carbon material C S12 and a fibrous conductive carbon material C having an average particle size of more than 1.15 μm. L12 and the index represented by the following formula 12 12 The fibrous conductive carbon material mixture is mixed in a ratio of 0.85 to 1.15. 12 and preparing the fibrous conductive carbon material mixture. 12 is added to the active material. Formula 12: Index 12 = (the fibrous conductive carbon material C S12 × the average particle size of the fibrous conductive carbon material C S12 Addition amount (%) of the fibrous conductive carbon material C L12 × the average particle size of the fibrous conductive carbon material C L12 (%) / 100 (1-3) When the average particle diameter of the fibrous conductive carbon material is more than 1.15 μm, the fibrous conductive carbon material C L13 and a fibrous conductive carbon material C having an average particle size of less than 0.85 μm. S13 and the index represented by the following formula 13 13 The fibrous conductive carbon material mixture is mixed in a ratio of 0.85 to 1.15. 13 and preparing the fibrous conductive carbon material mixture. 13 is added to the active material. Formula 13: Index 13 = (the fibrous conductive carbon material C L13 × the average particle size of the fibrous conductive carbon material C L13 Addition amount (%) of the fibrous conductive carbon material C S13 × the average particle size of the fibrous conductive carbon material C S13 (%) / 100 (2) The average particle size of the active material is greater than 6.5 μm and less than 7.5 μm. (2-1) When the average particle diameter of the fibrous conductive carbon material is 0.95 μm or more and 1.15 μm or less, the fibrous conductive carbon material C 21 is added to the active material. (2-2) When the average particle diameter of the fibrous conductive carbon material is less than 0.95 μm, the fibrous conductive carbon material C S22 and a fibrous conductive carbon material C having an average particle size of more than 1.15 μm. L22 and the index represented by the following formula 22 22 The fibrous conductive carbon material mixture is mixed in a ratio of 0.95 to 1.15. 22 and preparing the fibrous conductive carbon material mixture. 22 is added to the active material. Formula 22: Index 22 = (the fibrous conductive carbon material C S22 × the average particle size of the fibrous conductive carbon material C S22 Addition amount (%) of the fibrous conductive carbon material C L22 × the average particle size of the fibrous conductive carbon material C L22 (%) / 100 (2-3) When the average particle diameter of the fibrous conductive carbon material is more than 1.15 μm, the fibrous conductive carbon material C L23 and a fibrous conductive carbon material C having an average particle size of less than 0.95 μm. S23 and the index represented by the following formula 23 23 The fibrous conductive carbon material mixture is mixed in a ratio of 0.95 to 1.15. 23 and preparing the fibrous conductive carbon material mixture. 23 is added to the active material. Formula 23: Index 23 = (the fibrous conductive carbon material C L23 × the average particle size of the fibrous conductive carbon material C L23 Addition amount (%) of the fibrous conductive carbon material C S23 × the average particle size of the fibrous conductive carbon material C S23 (%) / 100 (3) The average particle size of the active material is greater than 7.5 μm and less than 8.5 μm. (3-1) When the average particle diameter of the fibrous conductive carbon material is 1.05 μm or more and 1.15 μm or less, the fibrous conductive carbon material C 31 is added to the active material. (3-2) When the average particle diameter of the fibrous conductive carbon material is less than 1.05 μm, the fibrous conductive carbon material C S32 and a fibrous conductive carbon material C having an average particle size of more than 1.15 μm. L32 and the index represented by the following formula 32 32 The fibrous conductive carbon material mixture is mixed in a ratio of 1.05 to 1.15. 32 and preparing the fibrous conductive carbon material mixture. 32 is added to the active material. Formula 32: Index 32 = (the fibrous conductive carbon material C S32 × the average particle size of the fibrous conductive carbon material C S32 Addition amount (%) of the fibrous conductive carbon material C L32 × the average particle size of the fibrous conductive carbon material C L32 (%) / 100 (3-3) When the average particle diameter of the fibrous conductive carbon material is more than 1.15 μm, the fibrous conductive carbon material C L33 and a fibrous conductive carbon material C having an average particle size of less than 1.05 μm. S33 and the index represented by the following formula 33 33 The fibrous conductive carbon material mixture is mixed in a ratio of 1.05 to 1.15. 33 and preparing the fibrous conductive carbon material mixture. 33 is added to the active material. Formula 33: Index 33 = (the fibrous conductive carbon material C L33 × the average particle size of the fibrous conductive carbon material C L33 Addition amount (%) of the fibrous conductive carbon material C S33 × the average particle size of the fibrous conductive carbon material C S33 (%) / 100 <6> <1> ~ <5> 13. An electrode comprising an active material mixture obtained by the method for producing an active material mixture for an electrode according to claim 12. <7> <6> A battery having the electrode according to claim 1. Effect of the Invention

[0008] According to one embodiment of the present disclosure, there is provided a method for producing an active material mixture for an electrode which results in an electrode having excellent through-hole resistance and battery resistance, an electrode including the active material mixture obtained by the method for producing the active material mixture, and a battery. [Brief description of the drawings]

[0009] [Figure 1] FIG. 1 is a schematic cross-sectional view illustrating an example of a secondary battery according to an embodiment of the present disclosure. [Diagram 2] FIG. 2 is a schematic cross-sectional view showing the configuration of an apparatus used to measure penetration resistance in the examples. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0010] Hereinafter, an embodiment that is an example of the present disclosure will be described. These descriptions and examples are merely illustrative of the embodiment, and are not intended to limit the scope of the invention. In the present specification, the upper or lower limit of one numerical range may be replaced with the upper or lower limit of another numerical range. In addition, in the present specification, the upper or lower limit of the numerical range may be replaced with a value shown in the examples.

[0011] Each component may contain multiple types of the corresponding substance. When referring to the amount of each component in a composition, if the composition contains multiple substances corresponding to each component, the amount refers to the total amount of those multiple substances present in the composition, unless otherwise specified.

[0012] <Method of manufacturing active material mixture for electrodes> A method for producing an active material mixture for an electrode according to an embodiment of the present disclosure (hereinafter also simply referred to as a "method for producing an active material mixture") includes the steps of preparing an active material, preparing a fibrous conductive carbon material, and adding the fibrous conductive carbon material to the active material according to the conditions (i) to (iii) below. (i) When the average particle size of the fibrous conductive carbon material is equal to or larger than criterion A and equal to or smaller than criterion B, the fibrous conductive carbon material is added to the active material. (ii) When the average particle size of the fibrous conductive carbon material is less than the criterion A, the fibrous conductive carbon material C Sii and a fibrous conductive carbon material C having an average particle size exceeding the standard B. Lii and mixing the fibrous conductive carbon material mixture. ii and preparing the fibrous conductive carbon material mixture. ii is added to the active material. (iii) When the average particle size of the fibrous conductive carbon material exceeds the criterion B, the fibrous conductive carbon material C Liii and a fibrous conductive carbon material C having an average particle size less than the standard A. Siii and mixing the fibrous conductive carbon material mixture. iii and preparing the fibrous conductive carbon material mixture. iii is added to the active material.

[0013] A conductive assistant has been conventionally added to the active material used in the electrode in order to improve the performance of the electrode (e.g., improve the conductivity). As the conductive assistant added to the active material, for example, a fibrous conductive carbon material such as carbon nanotubes is used. However, the fibrous conductive carbon material generally has a large variation in particle size, for example, the carbon nanotubes distributed on the market have a large variation in particle size. The present inventors have found that the variation in particle size of the fibrous conductive carbon material added to the active material has a significant effect on the through resistance and battery resistance (direct current internal resistance of the battery: DC-IR). It was found that when a fibrous conductive carbon material with a small particle size is added, a network between the active materials is not well formed, and the penetration resistance and the battery resistance are deteriorated, whereas when a fibrous conductive carbon material with a large particle size is added, a network is not well formed within the active materials, and the battery resistance is deteriorated.

[0014] In response to this, in order to adjust the penetration resistance and battery resistance (DC-IR) to a suitable range, a method of selecting (e.g., sieving) only fibrous conductive carbon material having a particle size in a suitable range and using it is conceivable. However, if only fibrous conductive carbon material with a particle size in a suitable range is selected, fibrous conductive carbon material with a large or small particle size will be discarded without being used, which increases costs. In addition, an additional selection process (e.g., a sieving process) is required to select only those with a particle size in the suitable range, which also increases costs.

[0015] Therefore, in a manufacturing method for an active material mixture according to an embodiment of the present disclosure, rather than selecting and using only those fibrous conductive carbon materials having a particle size within a suitable range from among the prepared (e.g., obtained or produced) fibrous conductive carbon materials, we have discovered a method in which the fibrous conductive carbon material is added to the active material according to the conditions (i) to (iii) described above. As shown in condition (i), when the average particle diameter of the fibrous conductive carbon material is greater than or equal to criterion A and less than or equal to criterion B, that is, when the fibrous conductive carbon material has an average particle diameter within a suitable range from the standpoint of the through resistance and battery resistance (DC-IR), the fibrous conductive carbon material is used as is and added to the active material. Furthermore, as shown in condition (ii), when the average particle diameter of the fibrous conductive carbon material is less than criterion A, that is, when the average particle diameter of the fibrous conductive carbon material is smaller than the preferred range from the standpoint of the penetration resistance and battery resistance (DC-IR), the fibrous conductive carbon material is mixed with a fibrous conductive carbon material having an average particle diameter larger than the preferred range to prepare a mixture, and the mixture is added to the active material. Furthermore, as shown in condition (iii), when the average particle diameter of the fibrous conductive carbon material exceeds criterion B, i.e., when the average particle diameter of the fibrous conductive carbon material is larger than the suitable range from the standpoint of the penetration resistance and battery resistance (DC-IR), it is mixed with a fibrous conductive carbon material having an average particle diameter smaller than the suitable range to prepare a mixture, and the mixture is added to the active material. It has been found that by adding the fibrous conductive carbon material to the active material according to the conditions (i) to (iii) above, an electrode having excellent through-hole resistance and battery resistance (DC-IR) can be obtained without having to select only those fibrous conductive carbon material having a particle size within a suitable range.

[0016] The "criterion A" and "criterion B" for the average particle size of the fibrous conductive carbon material may be determined according to the required penetration resistance and battery resistance (DC-IR).

[0017] Here, an example of a method for predetermining criteria A and B regarding the average particle diameter of the fibrous conductive carbon material will be described.

[0018] (Method for determining Criteria A and Criteria B [1]) A fibrous conductive carbon material is mixed with an active material to prepare an active material mixture, and then a battery is prepared using the active material mixture to measure the battery resistance. This is carried out for three or more types of fibrous conductive carbon materials having different average particle sizes. Then, a graph is created showing the correlation between the average particle size of the fibrous conductive carbon material and the battery resistance. The average particle sizes of the fibrous conductive carbon material in the range in which the battery resistance exceeds a certain value in the graph are defined as the criterion A and criterion B.

[0019] By determining criteria A and B by the determination method [1] and then producing an active material mixture by the method for producing an active material mixture according to the embodiment of the present disclosure described above, an electrode having excellent penetration resistance and battery resistance (DC-IR) can be obtained without selecting and using only those fibrous conductive carbon materials having a particle size within a suitable range from the prepared fibrous conductive carbon material.

[0020] In the determination method [1], the active materials used are the same type and have the same average particle size. The amount of fibrous conductive carbon material added to the active materials is also the same.

[0021] In the determination method [1], the more types of fibrous conductive carbon materials (fibrous conductive carbon materials having different average particle sizes) are used, the more preferable. For example, it is preferable to prepare the graph using 5 or more types of fibrous conductive carbon materials, and it is more preferable to prepare the graph using 10 or more types of fibrous conductive carbon materials.

[0022] The "constant value" of the battery resistance in the determination method [1] may be determined according to the battery resistance (DC-IR) required for the battery to be manufactured.

[0023] When determining in advance the criteria A and B for the average particle diameter of the fibrous conductive carbon material, it is more preferable to create a correlation graph using active materials having different average particle diameters. An example of this method will be described.

[0024] (Method of determining Criteria A and Criteria B [2]) The fibrous conductive carbon material is mixed with an active material to prepare an active material mixture, and then a battery is prepared using the active material mixture to measure the battery resistance. This is carried out for three or more types of the fibrous conductive carbon material having different average particle diameters and three or more types of the active material having different average particle diameters. Then, a graph showing the correlation between the average particle diameter of the fibrous conductive carbon material and the battery resistance is created for each average particle diameter of the active material. The average particle diameters of the fibrous conductive carbon material within a range in which the battery resistance exceeds a certain value in the graph for each average particle diameter of the active material are defined as criterion A and criterion B.

[0025] In the determination method [2], the number of graphs is the same as the number of types of active materials used (the number of active materials with different average particle diameters). That is, a different graph is created for each average particle diameter of the active materials used in the determination method [2], and criterion A and criterion B are determined for each graph. Therefore, when producing an active material mixture by the method for producing an active material mixture according to the embodiment of the present disclosure described above, the average particle diameter of the active material is confirmed (for example, the average particle diameter of the active material is measured in advance), and the active material mixture is produced based on criterion A and criterion B according to the average particle diameter. For example, the average particle diameter of the active material is confirmed, and the active material mixture can be produced based on criterion A and criterion B determined by the graph created using an active material having an average particle diameter closest to the confirmed average particle diameter. In this manner, by determining criteria A and B by the determination method [2], and then producing an active material mixture by the method for producing an active material mixture according to the embodiment of the present disclosure described above, an electrode having excellent penetration resistance and battery resistance (DC-IR) can be obtained without selecting and using only those fibrous conductive carbon materials having a particle size within a suitable range.

[0026] In the determination method [2], the same type of active material is used, and the amount of fibrous conductive carbon material added to the active material is also the same.

[0027] In the determination method [2], the more types of fibrous conductive carbon materials (fibrous conductive carbon materials having different average particle sizes) are used, the more preferable. For example, it is preferable to prepare the graph using 5 or more types of fibrous conductive carbon materials, and it is more preferable to prepare the graph using 10 or more types of fibrous conductive carbon materials. In the determination method [2], the more types of active materials (active materials having different average particle sizes) are used, the more preferable. For example, it is preferable to prepare the graph using five or more types of active materials, and it is more preferable to prepare the graph using ten or more types of fibrous conductive carbon materials.

[0028] The "constant value" of the battery resistance in the determination method [2] may be determined according to the battery resistance (DC-IR) required for the battery to be manufactured.

[0029] (Mixing ratio in fibrous conductive carbon material mixture) In the above-described method for producing an active material mixture according to an embodiment of the present disclosure, under the condition (ii), the average particle size of the fibrous conductive carbon material C is less than the standard A. Sii and a fibrous conductive carbon material C having an average particle size exceeding standard B. Lii and mixing the fibrous conductive carbon material mixture. ii In addition, under the condition (iii), a fibrous conductive carbon material C having an average particle size exceeding the standard B is prepared. Liii and a fibrous conductive carbon material C having an average particle size less than standard A. Siii and mixing the fibrous conductive carbon material mixture. iii The fibrous conductive carbon material mixture is prepared as follows: ii Fibrous conductive carbon material C Sii and C. Lii and the mixture ratio of the fibrous conductive carbon material iii Fibrous conductive carbon material C Liii and C. Siii The mixing ratio of the fibrous conductive carbon material and the fibrous conductive carbon material is not particularly limited. Regardless of the mixing ratio at which the fibrous conductive carbon material mixture is prepared, the penetration resistance and the battery resistance (DC-IR) can be improved.

[0030] However, from the viewpoint of obtaining an electrode having better penetration resistance and battery resistance (DC-IR), it is preferable to prepare a fibrous conductive carbon material mixture by the following method when the fibrous conductive carbon material is added to the active material under the above condition (ii) or the above condition (iii).

[0031] Under the condition (ii) above, an index represented by the following formula ii is ii is equal to or greater than criterion A and equal to or less than criterion B, Sii and fibrous conductive carbon material C Lii and mixing the fibrous conductive carbon material mixture. ii Prepare the following: Formula ii: Index ii = (the fibrous conductive carbon material C Sii × the average particle size of the fibrous conductive carbon material C Sii Addition amount (%) of the fibrous conductive carbon material C Lii × the average particle size of the fibrous conductive carbon material C Lii (%) / 100

[0032] Under the condition (iii) above, an index represented by the following formula iii is iii is equal to or greater than criterion A and equal to or less than criterion B, Siii and fibrous conductive carbon material C Liii and mixing the fibrous conductive carbon material mixture. iii Prepare the following: Formula III: Index iii = (the fibrous conductive carbon material C Liii × the average particle size of the fibrous conductive carbon material C Liii Addition amount (%) of the fibrous conductive carbon material C Siii × the average particle size of the fibrous conductive carbon material C Siii (%) / 100

[0033] By preparing a fibrous conductive carbon material mixture by the above-mentioned method under condition (ii) or condition (iii), and then producing an active material mixture by the method for producing an active material mixture according to the embodiment of the present disclosure described above, an electrode having better penetration resistance and battery resistance (DC-IR) can be obtained without having to select and use only those fibrous conductive carbon materials having a particle size within a suitable range from the prepared fibrous conductive carbon material.

[0034] (One example of a method for producing an active material mixture) Here, an example of a method for producing an active material mixture according to an embodiment of the present disclosure will be described.

[0035] An example of a method for producing an active material mixture according to an embodiment of the present disclosure includes the following steps. A step of preparing an active material having an average particle size of 4.5 μm or more and 8.5 μm or less. A step of preparing a fibrous conductive carbon material having an average particle size of 0.75 μm or more and 1.35 μm or less. Adding the fibrous conductive carbon material to the active material according to the following conditions (1) to (3):

[0036] (1) The average particle size of the active material is 4.5 μm or more and 6.5 μm or less. (1-1) When the average particle diameter of the fibrous conductive carbon material is 0.85 μm or more and 1.15 μm or less, the fibrous conductive carbon material C 11 is added to the active material. (1-2) When the average particle diameter of the fibrous conductive carbon material is less than 0.85 μm, the fibrous conductive carbon material C S12 and a fibrous conductive carbon material C having an average particle size of more than 1.15 μm. L12 and the index represented by the following formula 12 12 The fibrous conductive carbon material mixture is mixed in a ratio of 0.85 to 1.15. 12 and preparing the fibrous conductive carbon material mixture. 12 is added to the active material. Formula 12: Index 12 = (the fibrous conductive carbon material C S12 × the average particle size of the fibrous conductive carbon material C S12 Addition amount (%) of the fibrous conductive carbon material C L12 × the average particle size of the fibrous conductive carbon material C L12 (%) / 100 (1-3) When the average particle diameter of the fibrous conductive carbon material is more than 1.15 μm, the fibrous conductive carbon material C L13 and a fibrous conductive carbon material C having an average particle size of less than 0.85 μm. S13 and the index represented by the following formula 13 13 The fibrous conductive carbon material mixture is mixed in a ratio of 0.85 to 1.15. 13 and preparing the fibrous conductive carbon material mixture. 13 is added to the active material. Formula 13: Index 13 = (the fibrous conductive carbon material C L13 × the average particle size of the fibrous conductive carbon material CL13 Addition amount (%) of the fibrous conductive carbon material C S13 × the average particle size of the fibrous conductive carbon material C S13 (%) / 100

[0037] (2) The average particle size of the active material is greater than 6.5 μm and less than 7.5 μm. (2-1) When the average particle diameter of the fibrous conductive carbon material is 0.95 μm or more and 1.15 μm or less, the fibrous conductive carbon material C 21 is added to the active material. (2-2) When the average particle diameter of the fibrous conductive carbon material is less than 0.95 μm, the fibrous conductive carbon material C S22 and a fibrous conductive carbon material C having an average particle size of more than 1.15 μm. L22 and the index represented by the following formula 22 22 The fibrous conductive carbon material mixture is mixed in a ratio of 0.95 to 1.15. 22 and preparing the fibrous conductive carbon material mixture. 22 is added to the active material. Formula 22: Index 22 = (the fibrous conductive carbon material C S22 × the average particle size of the fibrous conductive carbon material C S22 Addition amount (%) of the fibrous conductive carbon material C L22 × the average particle size of the fibrous conductive carbon material C L22 (%) / 100 (2-3) When the average particle diameter of the fibrous conductive carbon material is more than 1.15 μm, the fibrous conductive carbon material C L23 and a fibrous conductive carbon material C having an average particle size of less than 0.95 μm. S23 and the index represented by the following formula 23 23 The fibrous conductive carbon material mixture is mixed in a ratio of 0.95 to 1.15. 23 and preparing the fibrous conductive carbon material mixture. 23 is added to the active material. Formula 23: Index 23 = (the fibrous conductive carbon material C L23 × the average particle size of the fibrous conductive carbon material C L23Addition amount (%) of the fibrous conductive carbon material C S23 × the average particle size of the fibrous conductive carbon material C S23 (%) / 100

[0038] (3) The average particle size of the active material is greater than 7.5 μm and less than 8.5 μm. (3-1) When the average particle diameter of the fibrous conductive carbon material is 1.05 μm or more and 1.15 μm or less, the fibrous conductive carbon material C 31 is added to the active material. (3-2) When the average particle diameter of the fibrous conductive carbon material is less than 1.05 μm, the fibrous conductive carbon material C S32 and a fibrous conductive carbon material C having an average particle size of more than 1.15 μm. L32 and the index represented by the following formula 32 32 The fibrous conductive carbon material mixture is mixed in a ratio of 1.05 to 1.15. 32 and preparing the fibrous conductive carbon material mixture. 32 is added to the active material. Formula 32: Index 32 = (the fibrous conductive carbon material C S32 × the average particle size of the fibrous conductive carbon material C S32 Addition amount (%) of the fibrous conductive carbon material C L32 × the average particle size of the fibrous conductive carbon material C L32 (%) / 100 (3-3) When the average particle diameter of the fibrous conductive carbon material is more than 1.15 μm, the fibrous conductive carbon material C L33 and a fibrous conductive carbon material C having an average particle size of less than 1.05 μm. S33 and the index represented by the following formula 33 33 The fibrous conductive carbon material mixture is mixed in a ratio of 1.05 to 1.15. 33 and preparing the fibrous conductive carbon material mixture. 33 is added to the active material. Formula 33: Index 33 = (the fibrous conductive carbon material C L33 × the average particle size of the fibrous conductive carbon material C L33Addition amount (%) of the fibrous conductive carbon material C S33 × the average particle size of the fibrous conductive carbon material C S33 (%) / 100

[0039] Thus, in one example of a method for producing an active material mixture according to an embodiment of the present disclosure, first, in the steps of preparing an active material and preparing a fibrous conductive carbon material, an active material having an average particle diameter of 4.5 μm or more and 8.5 μm or less, and a fibrous conductive carbon material having an average particle diameter of 0.75 μm or more and 1.35 μm or less are prepared. Then, in the step of adding the fibrous conductive carbon material to the active material, a prepared (e.g., obtained or produced) active material and fibrous conductive carbon material are used, and the fibrous conductive carbon material is added to the active material according to the conditions (1) to (3) above.

[0040] Condition (1) is applied when the average particle diameter of the active material is 4.5 μm or more and 6.5 μm or less. As shown in condition (1-1), when the average particle diameter of the fibrous conductive carbon material is 0.85 μm (criterion A) or more and 1.15 μm (criterion B) or less, the fibrous conductive carbon material C is used as it is. 11 is added to the active material using In addition, as shown in condition (1-2), when the average particle diameter of the fibrous conductive carbon material is less than 0.85 μm (criterion A), the fibrous conductive carbon material C having an average particle diameter of less than 0.85 μm (criterion A) is S12 and fibrous conductive carbon material C having an average particle size of more than 1.15 μm (criterion B). L12 and mixing the fibrous conductive carbon material mixture. 12 In this case, the index represented by the formula 12 is prepared. 12 The ratio of the fibrous conductive carbon material C is 0.85 or more and 1.15 or less. S12 and C. L12 Then, the fibrous conductive carbon material mixture is 12 is added to the active material. Furthermore, as shown in condition (1-3), when the average particle diameter of the fibrous conductive carbon material is more than 1.15 μm (criterion B), the fibrous conductive carbon material C having this average particle diameter more than 1.15 μm (criterion B)L13 and fibrous conductive carbon material C having an average particle size of less than 0.85 μm (criterion A). S13 and mixing the fibrous conductive carbon material mixture. 13 In this case, the index represented by the formula 13 is prepared. 13 The ratio of the fibrous conductive carbon material C is 0.85 or more and 1.15 or less. L13 and C. S13 Then, the fibrous conductive carbon material mixture is 13 is added to the active material.

[0041] Condition (2) is applied when the average particle diameter of the active material is more than 6.5 μm and not more than 7.5 μm. As shown in condition (2-1), when the average particle diameter of the fibrous conductive carbon material is 0.95 μm (criterion A) or more and 1.15 μm (criterion B) or less, the fibrous conductive carbon material C is used as it is. 21 is added to the active material using In addition, as shown in condition (2-2), when the average particle diameter of the fibrous conductive carbon material is less than 0.95 μm (criterion A), the fibrous conductive carbon material C having an average particle diameter of less than 0.95 μm (criterion A) is S22 and fibrous conductive carbon material C having an average particle size of more than 1.15 μm (criterion B). L22 and mixing the fibrous conductive carbon material mixture. 22 In this case, the index represented by the formula 22 is prepared. 22 is 0.95 or more and 1.15 or less, S22 and C. L22 Then, the fibrous conductive carbon material mixture is 22 is added to the active material. Furthermore, as shown in condition (2-3), when the average particle diameter of the fibrous conductive carbon material is more than 1.15 μm (criterion B), the fibrous conductive carbon material C having this average particle diameter more than 1.15 μm (criterion B) L23 and fibrous conductive carbon material C having an average particle size of less than 0.95 μm (criterion A). S23 and mixing the fibrous conductive carbon material mixture. 23 In this case, the index represented by the formula 23 is prepared. 23is 0.95 or more and 1.15 or less, L23 and C. S23 Then, the fibrous conductive carbon material mixture is 23 is added to the active material.

[0042] Condition (3) is applied when the average particle diameter of the active material is more than 7.5 μm and not more than 8.5 μm. As shown in condition (3-1), when the average particle diameter of the fibrous conductive carbon material is 1.05 μm (criterion A) or more and 1.15 μm (criterion B) or less, the fibrous conductive carbon material C is used as it is. 31 is added to the active material using In addition, as shown in condition (3-2), when the average particle diameter of the fibrous conductive carbon material is less than 1.05 μm (criterion A), the fibrous conductive carbon material C having an average particle diameter of less than 1.05 μm (criterion A) is S32 and fibrous conductive carbon material C having an average particle size of more than 1.15 μm (criterion B). L32 and mixing the fibrous conductive carbon material mixture. 32 In this case, the index represented by formula 32 is prepared. 32 is 1.05 or more and 1.15 or less, S32 and C. L32 Then, the fibrous conductive carbon material mixture is 32 is added to the active material. Furthermore, as shown in condition (3-3), when the average particle diameter of the fibrous conductive carbon material is more than 1.15 μm (criterion B), the fibrous conductive carbon material C having this average particle diameter of more than 1.15 μm (criterion B) L33 and fibrous conductive carbon material C having an average particle size of less than 1.05 μm (criterion A). S33 and mixing the fibrous conductive carbon material mixture. 33 In this case, the index represented by formula 33 is prepared. 33 The ratio of the fibrous conductive carbon material C is 1.05 or more and 1.15 or less. L33 and C. S33 Then, the fibrous conductive carbon material mixture is 33 is added to the active material.

[0043] By adding the fibrous conductive carbon material to the active material according to the conditions (1) to (3) above, an electrode having excellent through resistance and battery resistance (DC-IR) can be obtained without having to select only those fibrous conductive carbon material having a particle size within a suitable range.

[0044] (Method of measuring average particle size) The average particle size of the active material can be measured using a laser diffraction particle size distribution analyzer (LA-960, laser diffraction / scattering particle size distribution analyzer, manufactured by Horiba, Ltd.). The average particle size of the fibrous conductive carbon material can be measured by dynamic light scattering (DLS). Note that the measurement of the average particle size by DLS is specified in ISO 22412 (2017).

[0045] -Active material- In the method for producing an active material mixture according to an embodiment of the present disclosure, an active material mixture is produced using at least an active material and a fibrous conductive carbon material. Active materials include positive electrode active materials used in the positive electrode of a battery, and negative electrode active materials used in the negative electrode.

[0046] The positive electrode active material is, for example, a material capable of absorbing and releasing lithium ions. Examples of the positive electrode active material include lithium nickel oxides, lithium cobalt oxides (e.g., LiCoO2, etc.), and lithium manganese oxides (e.g., LiMn2O4). Examples of the lithium nickel oxides include LiCoO2, ternary lithium transition metal oxides, and solid-solution type lithium-excess transition metal oxides. Ternary lithium transition metal oxides are represented by the general formula (A): Li(Li a Mn x Co y Ni z )O2 (where a, x, y, and z in formula (A) satisfy a+x+y+z≒1 and xyz≠0). Solid-solution lithium-rich transition metal oxides are represented by the general formula (B): xLi[Li 1 / 3 Mn 2 / 3It is represented by O2·(1-x)LiMeO2 (in formula (B), Me is one or more transition metals, and x satisfies 0 < x ≤ 1).

[0047] The negative electrode active material is, for example, a material capable of occluding and releasing lithium ions (such as a carbon material (such as natural graphite, artificial graphite, etc.)).

[0048] In the method for producing an active material mixture according to an embodiment of the present disclosure, either the positive electrode active material or the negative electrode active material can be used as the active material, but it is preferable to mix the positive electrode active material and the fibrous conductive carbon material to produce an active material mixture for the positive electrode.

[0049] From the viewpoint of obtaining an electrode having excellent through - resistance and battery resistance (DC - IR), the average particle diameter of the active material used in the embodiment of the present disclosure is preferably, for example, 1.0 μm or more and 15.0 μm or less, more preferably 3.0 μm or more and 10.0 μm or less, and still more preferably 4.5 μm or more and 8.5 μm or less.

[0050] - Fibrous conductive carbon material - The fibrous conductive carbon material is a fibrous and conductive material containing a carbon material. Examples of the carbon material include carbon nanotubes, carbon fibers, carbon nanofibers, etc. Among these, carbon nanotubes are preferable from the viewpoint of obtaining an electrode having excellent through - resistance and battery resistance (DC - IR).

[0051] Carbon nanotubes can be synthesized by any method, for example, by arc discharge method, laser ablation method, CVD method, etc.

[0052] In the step of preparing the fibrous conductive carbon material in the method for producing an active material mixture according to an embodiment of the present disclosure, for example, the fibrous conductive carbon material may be produced, or it may be obtained (for example, by purchasing products sold on the market).

[0053] The average particle diameter of the fibrous conductive carbon material used in an embodiment of the present disclosure is, from the viewpoint of obtaining an electrode having excellent penetration resistance and battery resistance (DC-IR), preferably 0.50 μm or more and 1.60 μm or less, more preferably 0.60 μm or more and 1.40 μm or less, and even more preferably 0.75 μm or more and 1.35 μm or less.

[0054] In the manufacturing method of an active material mixture according to an embodiment of the present disclosure, the amount of fibrous conductive carbon material added (note that in the case of fibrous conductive carbon material, this refers to the total amount, and in the case of adding a fibrous conductive carbon material mixture, it means the total amount of the mixed fibrous conductive carbon material) is preferably 0.1 mass % or more and 2.0 mass % or less, more preferably 0.2 mass % or more and 1.5 mass % or less, and even more preferably 0.3 mass % or more and 1.0 mass % or less, relative to the amount of active material.

[0055] <Electrode> The electrodes according to the embodiments of the present disclosure include an active material mixture obtained by the method for producing an active material mixture according to the embodiments of the present disclosure. Specifically, the active material mixture is included in the active material layers of the positive electrode and the negative electrode.

[0056] The electrode according to the embodiment of the present disclosure can be used as either a positive electrode or a negative electrode, but is preferably used as a positive electrode.

[0057] The active material layer in the electrode contains the active material mixture and may contain, for example, a binder in addition to the active material mixture. The active material layer includes a positive electrode active material layer and a negative electrode active material layer.

[0058] The positive electrode active material layer contains, for example, a positive electrode active material and a positive electrode binder. Examples of the positive electrode active material include the active materials described above. Examples of the positive electrode binder include fluororesins (for example, polyvinylidene fluoride, tetrafluoroethylene-hexafluoropropylene copolymer, etc.), polyvinyl acetate, and the like. The positive electrode active material layer may contain, as necessary, a conductive assistant other than the fibrous conductive carbon material (for example, acetylene black, etc.), a thickener, a surfactant, a dispersant, a wetting agent, an antifoaming agent, and the like.

[0059] The negative electrode active material layer contains, for example, a negative electrode active material and a negative electrode binder. Examples of the negative electrode active material include the active materials described above. Examples of the negative electrode binder include fluororesins (for example, polyvinylidene fluoride (PVdF), tetrafluoroethylene-hexafluoropropylene copolymer, etc.), polyvinyl acetate, and the like. The negative electrode active material layer may contain, as necessary, a conductive assistant (eg, acetylene black, etc.) other than the fibrous conductive carbon material, a thickener, a surfactant, a dispersant, a wetting agent, an antifoaming agent, and the like.

[0060] <Battery> The battery according to the embodiment of the present disclosure has an electrode according to the embodiment of the present disclosure. For example, the battery according to the embodiment of the present disclosure has a positive electrode, a negative electrode, and a separator interposed between the positive electrode and the negative electrode, and has the electrode according to the embodiment of the present disclosure as at least one of the positive electrode and the negative electrode.

[0061] Here, an example of a battery according to an embodiment of the present disclosure will be described with reference to FIG. 1. A secondary battery 100, which is an example of a battery, has a positive electrode including a positive electrode current collector 32 (e.g., aluminum foil, etc.) and a positive electrode active material layer 34 including a positive electrode active material formed on both sides of the positive electrode current collector 32. The secondary battery 100 also has a negative electrode including a negative electrode current collector 22 (e.g., copper foil, etc.) and a negative electrode active material layer 24 including a negative electrode active material formed on both sides of the negative electrode current collector 22. The secondary battery 100 has a structure in which a positive electrode and a negative electrode are laminated with a separator 60 interposed therebetween. The secondary battery 100 is configured to include predetermined battery constituent materials (active materials for the positive and negative electrodes, current collectors for the positive and negative electrodes, a separator, etc.) like a typical lithium secondary battery. At least one of the positive electrode active material layer 34 and the negative electrode active material layer 24 includes an active material mixture obtained by the manufacturing method for an active material mixture according to an embodiment of the present disclosure described above.

[0062] The positive electrode current collector is a metal foil (for example, aluminum foil, etc.). The details of the positive electrode active material layer are the same as those of the electrode body already described, and therefore will not be described here.

[0063] The negative electrode current collector may be, for example, copper foil. The details of the negative electrode active material layer are the same as those of the electrode body already described, and therefore will not be described here.

[0064] The separator may be, for example, a porous resin flat plate, and the material of the resin flat plate may be resin (for example, polyethylene, polypropylene, etc.).

[0065] The electrolyte used in the battery is preferably, for example, a non-aqueous electrolyte. The non-aqueous electrolyte contains an electrolyte and a non-aqueous solvent. The electrolyte may be a lithium salt containing fluorine (e.g., lithium hexafluorophosphate, lithium tetrafluoroborate, etc.), a lithium salt not containing fluorine (e.g., lithium perchlorate, lithium tetrachloroaluminate, etc.), or the like. The non-aqueous solvent may be a cyclic carbonate (e.g., ethylene carbonate, etc.), a chain carbonate (e.g., dimethyl carbonate, ethyl methyl carbonate, etc.), or the like. The non-aqueous electrolyte may further contain an additive (e.g., lithium bis(oxalato)borate, etc.). EXAMPLES

[0066] Examples will be described below, but the present invention is not limited to these examples. In the following description, unless otherwise specified, all "parts" and "%" are based on mass.

[0067] <Determination of Criterion A and Criterion B> A total of four types of positive electrode active materials (material: lithium transition metal oxide) having average particle sizes of 5.0 μm, 6.0 μm, 7.0 μm, and 8.0 μm were prepared. Furthermore, a total of six types of carbon nanotubes (manufactured by Sigma Aldrich, product name: multi-walled carbon nanotubes) having average particle sizes of 0.8 μm, 0.9 μm, 1.0 μm, 1.1 μm, 1.2 μm, and 1.3 μm were prepared.

[0068] Each of the prepared active materials and carbon nanotubes was mixed with a binder (polyvinylidene fluoride: PVdF) in a ratio (mass ratio) of active material:carbon nanotubes:PVdF = 98.5:0.5:1 to obtain a total of 24 types of active material mixtures for determining standards (standard determination samples).

[0069] Each of the reference determination samples was applied to both sides of a positive electrode current collector (aluminum foil) to form a positive electrode composite layer, thereby forming an electrode (positive electrode). The penetration resistance of this electrode was measured by the following method. 2, the through resistance of the electrode was measured by sandwiching an electrode having a positive electrode composite layer 44 on both sides of a positive electrode current collector 42 with gold-plated terminals 46 disposed on both sides of the electrode. Next, the resistance value (AC-IR) by an AC method was measured with an AC-IR measuring device 48 connected to the terminals 46 on both sides.

[0070] Next, a secondary battery was formed having the electrode (positive electrode), a negative electrode including a negative electrode current collector (copper foil) and a negative electrode active material (material: graphite), and a separator. The battery resistance (battery direct current internal resistance: DC-IR) of the formed secondary battery was measured at 25° C., SOC (State of Charge) 50%, and C rates of 0.3C, 1C, and 3C.

[0071] In the standard determination samples using active materials with average particle sizes of 5.0 μm and 6.0 μm, the through resistance and DC-IR were both within the standard values ​​when carbon nanotubes with average particle sizes of 0.9 μm, 1.0 μm, and 1.1 μm were used, the through resistance and DC-IR both exceeded the standard values ​​when carbon nanotubes with an average particle size of 0.8 μm were used, and the DC-IR exceeded the standard value when carbon nanotubes with average particle sizes of 1.2 μm and 1.3 μm were used. Therefore, in the case of using an active material with an average particle diameter of 4.5 μm or more and 6.5 μm or less, criterion A for the average particle diameter of carbon nanotubes was determined to be "0.85 μm" and criterion B was determined to be "1.15 μm."

[0072] In the standard determination sample using active material with an average particle diameter of 7.0 μm, the through resistance and DC-IR were both within the standard values ​​when carbon nanotubes with average particle diameters of 1.0 μm and 1.1 μm were used, the through resistance and DC-IR both exceeded the standard values ​​when carbon nanotubes with average particle diameters of 0.8 μm and 0.9 μm were used, and the DC-IR exceeded the standard value when carbon nanotubes with average particle diameters of 1.2 μm and 1.3 μm were used. Therefore, in the case of using an active material with an average particle diameter of more than 6.5 μm and not more than 7.5 μm, criterion A for the average particle diameter of carbon nanotubes was determined to be "0.95 μm" and criterion B was determined to be "1.15 μm."

[0073] In the standard determination sample using active material with an average particle diameter of 8.0 μm, when carbon nanotubes with an average particle diameter of 1.1 μm were used, both the through resistance and DC-IR were within the standard values, when carbon nanotubes with average particle diameters of 0.8 μm, 0.9 μm, and 1.0 μm were used, and when carbon nanotubes with average particle diameters of 1.2 μm and 1.3 μm were used, DC-IR exceeded the standard value. Therefore, in the case of using an active material with an average particle diameter of more than 7.5 μm and 8.5 μm or less, criterion A for the average particle diameter of carbon nanotubes was determined to be "1.05 μm" and criterion B was determined to be "1.15 μm."

[0074] The criteria A and B thus determined are summarized in the following Table 1. In Table 1, the notation "Condition (○-○)" refers to the conditions (1-1) to (1-3), (2-1) to (2-3), and (3-1) to (3-3) in the above-mentioned (one example of a method for producing an active material mixture).

[0075] [Table 1]

[0076] <Examples and Comparative Examples> (Preparation of active material and carbon nanotubes) As a positive electrode active material (material: lithium transition metal oxide), an active material having an average particle size of 6.0 μm was prepared. Furthermore, as the carbon nanotubes (same as above), three types of carbon nanotubes having average particle sizes of 0.8 μm, 1.0 μm, and 1.2 μm were prepared.

[0077] Example 1 An active material having an average particle diameter of 6.0 μm, carbon nanotubes having an average particle diameter of 1.0 μm, and a binder (polyvinylidene fluoride: PVdF) were mixed in a ratio (mass ratio) of active material:carbon nanotubes:PVdF=98.5:0.5:1 to obtain an active material mixture of Example 1.

[0078] Comparative Example 1 An active material mixture of Comparative Example 1 was obtained in the same manner as in Example 1, except that the carbon nanotubes were changed to those having an average particle diameter of 0.8 μm.

[0079] Comparative Example 2 An active material mixture of Comparative Example 2 was obtained in the same manner as in Example 1, except that the carbon nanotubes were changed to those having an average particle diameter of 1.2 μm.

[0080] Example 2 An active material mixture of Example 2 was obtained in the same manner as in Example 1, except that the carbon nanotubes were changed to a mixed carbon nanotube having an average particle diameter of 0.8 μm and an average particle diameter of 1.2 μm mixed in a mass ratio of 1:1.

[0081] (evaluation) Using the active material mixture of each Example and Comparative Example, electrodes (positive electrodes) of each Example and Comparative Example were formed in the same manner as described above in <Determination of Criteria A and Criteria B>, and the through resistance (AC-IR) of these electrodes was measured by the method described above. In addition, secondary batteries were formed using the electrodes (positive electrodes) of each of the Examples and Comparative Examples in the same manner as in the above <Determination of Criteria A and Criteria B>, and the battery resistance (DC-IR) was measured.

[0082] Regarding the measured penetration resistance (AC-IR) and battery resistance (DC-IR), the ratios of Comparative Examples 1 to 2 and Example 2, with Example 1 set as the standard (100.0), are shown in Table 2 below.

[0083] [Table 2]

[0084] As shown in Table 2, in Example 2, carbon nanotubes having an average particle size less than the criterion A (0.8 μm) and carbon nanotubes having an average particle size greater than the criterion B (1.2 μm) were mixed and added to the active material. In Example 2, excellent through resistance and battery resistance (DC-IR) comparable to those of Example 1 were obtained. On the other hand, in Comparative Example 1, carbon nanotubes having an average particle size less than the above-mentioned standard A (0.8 μm) are added to the active material. In Comparative Example 1, both the penetration resistance and the battery resistance were inferior to those in Example 1. In Comparative Example 2, carbon nanotubes having an average particle size exceeding the above-mentioned standard B (1.2 μm) were added to the active material. In Comparative Example 2, the battery resistance was inferior to that in Example 1. [Explanation of symbols]

[0085] 22 Negative electrode current collector 24 Negative electrode active material layer 32 Secondary battery 34 Cathode active material layer 42 Positive electrode current collector 44 Positive electrode mixture layer 46 Terminals 48 AC-IR measuring machine 100 Secondary battery

Claims

1. Preparing an active material; Providing a fibrous conductive carbon material; adding the fibrous conductive carbon material to the active material according to the following conditions (i) to (iii); A method for producing an active material mixture for an electrode, comprising: (i) When the average particle size of the fibrous conductive carbon material is equal to or larger than criterion A and equal to or smaller than criterion B, the fibrous conductive carbon material is added to the active material. (ii) When the average particle diameter of the fibrous conductive carbon material is less than the criterion A, the fibrous conductive carbon material C Sii and a fibrous conductive carbon material C having an average particle size exceeding the standard B. Lii and mixing the fibrous conductive carbon material mixture. ii and preparing the fibrous conductive carbon material mixture. ii is added to the active material. (iii) When the average particle diameter of the fibrous conductive carbon material exceeds the criterion B, the fibrous conductive carbon material C Liii and a fibrous conductive carbon material C having an average particle size less than the standard A. Siii and mixing the fibrous conductive carbon material mixture. iii and preparing the fibrous conductive carbon material mixture. iii is added to the active material.

2. The method for producing an active material mixture for an electrode according to claim 1, wherein the criteria A and B are determined by the following determination method [1]. (Method for determining criteria A and B [1]) The fibrous conductive carbon material is mixed with an active material to prepare an active material mixture, and then a battery is prepared using the active material mixture to measure the battery resistance. This is carried out for three or more types of fibrous conductive carbon materials having different average particle sizes, and a graph is created showing the correlation between the average particle size of the fibrous conductive carbon material and the battery resistance. The average particle sizes of the fibrous conductive carbon material within a range in which the battery resistance exceeds a certain value in the graph are designated as criterion A and criterion B.

3. The method for producing an active material mixture for an electrode according to claim 1, wherein the criteria A and B are determined by the following determination method [2]. (Method for determining criteria A and B [2]) A fibrous conductive carbon material is mixed with an active material to prepare an active material mixture, and then a battery is prepared using the active material mixture to measure the battery resistance. This is performed for three or more types of fibrous conductive carbon materials having different average particle diameters, and for three or more types of active materials having different average particle diameters, and a graph showing the correlation between the average particle diameter of the fibrous conductive carbon material and the battery resistance is created for each average particle diameter of the active material. The average particle diameters of the fibrous conductive carbon material within the range in which the battery resistance exceeds a certain value in the graph for each average particle diameter of the active material are defined as criterion A and criterion B.

4. In the step of adding the fibrous conductive carbon material to the active material, Under the conditions shown in (ii) above, an index represented by the following formula ii ii is equal to or greater than the standard A and equal to or less than the standard B, Sii and the fibrous conductive carbon material C Lii and mixing the fibrous conductive carbon material mixture. ii Prepare Under the conditions shown in (iii) above, an index represented by the following formula iii iii is equal to or greater than the standard A and equal to or less than the standard B, Siii and the fibrous conductive carbon material C Liii and mixing the fibrous conductive carbon material mixture. iii preparing A method for producing the active material mixture for an electrode according to claim 1. Formula ii: indicator ii = (the fibrous conductive carbon material C Sii × the average particle size of the fibrous conductive carbon material C Sii + the amount (%) of the fibrous conductive carbon material C Lii × the average particle size of the fibrous conductive carbon material C Lii (amount added (%)) / 100 Formula iii: Index iii = (the fibrous conductive carbon material C Liii × the average particle size of the fibrous conductive carbon material C Liii + the amount (%) of the fibrous conductive carbon material C Siii × the average particle size of the fibrous conductive carbon material C Siii (amount added (%)) / 100

5. preparing an active material having an average particle size of 4.5 μm or more and 8.5 μm or less; preparing a fibrous conductive carbon material having an average particle size of 0.75 μm or more and 1.35 μm or less; adding the fibrous conductive carbon material to the active material according to the following conditions (1) to (3); A method for producing an active material mixture for an electrode, comprising: (1) The average particle size of the active material is 4.5 μm or more and 6.5 μm or less. (1-1) When the average particle diameter of the fibrous conductive carbon material is 0.85 μm or more and 1.15 μm or less, the fibrous conductive carbon material C 11 is added to the active material. (1-2) When the average particle diameter of the fibrous conductive carbon material is less than 0.85 μm, the fibrous conductive carbon material C S12 and a fibrous conductive carbon material C having an average particle size of more than 1.15 μm. L12 and an index represented by the following formula 12: 12 The fibrous conductive carbon material mixture is mixed in a ratio of 0.85 to 1.

15. 12 and preparing the fibrous conductive carbon material mixture. 12 is added to the active material. Formula 12: Index 12 = (the fibrous conductive carbon material C S12 × the average particle size of the fibrous conductive carbon material C S12 + the amount (%) of the fibrous conductive carbon material C L12 × the average particle size of the fibrous conductive carbon material C L12 (amount added (%)) / 100 (1-3) When the average particle diameter of the fibrous conductive carbon material is more than 1.15 μm, the fibrous conductive carbon material C L13 and a fibrous conductive carbon material C having an average particle size of less than 0.85 μm. S13 and an index represented by the following formula 13. 13 The fibrous conductive carbon material mixture is mixed in a ratio of 0.85 to 1.

15. 13 and preparing the fibrous conductive carbon material mixture. 13 is added to the active material. Formula 13: Index 13 = (the fibrous conductive carbon material C L13 × the average particle size of the fibrous conductive carbon material C L13 + the amount (%) of the fibrous conductive carbon material C S13 × the average particle size of the fibrous conductive carbon material C S13 (amount added (%)) / 100 (2) The average particle size of the active material is more than 6.5 μm and 7.5 μm or less. (2-1) When the average particle diameter of the fibrous conductive carbon material is 0.95 μm or more and 1.15 μm or less, the fibrous conductive carbon material C 21 is added to the active material. (2-2) When the average particle diameter of the fibrous conductive carbon material is less than 0.95 μm, the fibrous conductive carbon material C S22 and a fibrous conductive carbon material C having an average particle size of more than 1.15 μm. L22 and an index represented by the following formula 22: 22 The fibrous conductive carbon material mixture is mixed in a ratio of 0.95 to 1.

15. 22 and preparing the fibrous conductive carbon material mixture. 22 is added to the active material. Formula 22: Index 22 = (the fibrous conductive carbon material C S22 × the average particle size of the fibrous conductive carbon material C S22 + the amount (%) of the fibrous conductive carbon material C L22 × the average particle size of the fibrous conductive carbon material C L22 (amount added (%)) / 100 (2-3) When the average particle diameter of the fibrous conductive carbon material is more than 1.15 μm, the fibrous conductive carbon material C L23 and a fibrous conductive carbon material C having an average particle diameter of less than 0.95 μm. S23 and an index represented by the following formula 23: 23 The fibrous conductive carbon material mixture is mixed in a ratio of 0.95 to 1.

15. 23 and preparing the fibrous conductive carbon material mixture. 23 is added to the active material. Formula 23: Index 23 = (the fibrous conductive carbon material C L23 × the average particle size of the fibrous conductive carbon material C L23 + the amount (%) of the fibrous conductive carbon material C S23 × the average particle size of the fibrous conductive carbon material C S23 (amount added (%)) / 100 (3) The average particle size of the active material is more than 7.5 μm and 8.5 μm or less. (3-1) When the average particle diameter of the fibrous conductive carbon material is 1.05 μm or more and 1.15 μm or less, the fibrous conductive carbon material C 31 is added to the active material. (3-2) When the average particle diameter of the fibrous conductive carbon material is less than 1.05 μm, the fibrous conductive carbon material C S32 and a fibrous conductive carbon material C having an average particle size of more than 1.15 μm. L32 and an index represented by the following formula 32: 32 The fibrous conductive carbon material mixture is mixed in a ratio of 1.05 to 1.

15. 32 and preparing the fibrous conductive carbon material mixture. 32 is added to the active material. Formula 32: Index 32 = (the fibrous conductive carbon material C S32 × the average particle size of the fibrous conductive carbon material C S32 + the amount (%) of the fibrous conductive carbon material C L32 × the average particle size of the fibrous conductive carbon material C L32 (amount added (%)) / 100 (3-3) When the average particle diameter of the fibrous conductive carbon material is more than 1.15 μm, the fibrous conductive carbon material C L33 and a fibrous conductive carbon material C having an average particle size of less than 1.05 μm. S33 and an index represented by the following formula 33: 33 The fibrous conductive carbon material mixture is mixed in a ratio of 1.05 to 1.

15. 33 and preparing the fibrous conductive carbon material mixture. 33 is added to the active material. Formula 33: Index 33 = (the fibrous conductive carbon material C L33 × the average particle size of the fibrous conductive carbon material C L33 + the amount (%) of the fibrous conductive carbon material C S33 × the average particle size of the fibrous conductive carbon material C S33 (amount added (%)) / 100

6. An electrode comprising an active material mixture obtained by the method for producing an active material mixture for an electrode according to any one of claims 1 to 5.

7. A battery comprising the electrode according to claim 6.

Citation Information

Patent Citations

  • Negative electrode material, negative electrode, and lithium ion secondary battery

    WO2017061514A1